1999
DOI: 10.1002/(sici)1098-2361(1999)18:2<111::aid-zoo3>3.3.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive cycle length and pregnancy in the southern white rhinoceros (Ceratotherium simum simum) as determined by fecal pregnane analysis and observations of mating behavior

Abstract: Pregnancy and the reproductive cycle were monitored in 13 captive southern white rhinoceros (Ceratotherium simum simum) by measuring progesterone metabolites in fecal extracts and by observing behavior patterns. Fecal hormones were measured using a monoclonal antibody produced against 4-pregnen-11-o1-3,20-dione hemisuccinate:BSA. Several subjects exhibited flat or erratic endocrine profiles, but we found evidence for 17 reproductive cycles in five females. Mating behavior coincided with nadirs in pregnane conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
96
2
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(108 citation statements)
references
References 0 publications
9
96
2
1
Order By: Relevance
“…This technique thus facilitates the detection of pregnancy in wild individuals in a non-invasive way, which can also be useful for surveillance strategies and the detection of foetal death during pregnancy. The mean FPM profiles in wild southern white rhinoceroses found in this study resemble those found in captive white rhinoceros individuals (Schwarzenberger et al 1998;Patton et al 1999). The number of samples collected for this study was insufficient to detect ovarian cycling patterns.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…This technique thus facilitates the detection of pregnancy in wild individuals in a non-invasive way, which can also be useful for surveillance strategies and the detection of foetal death during pregnancy. The mean FPM profiles in wild southern white rhinoceroses found in this study resemble those found in captive white rhinoceros individuals (Schwarzenberger et al 1998;Patton et al 1999). The number of samples collected for this study was insufficient to detect ovarian cycling patterns.…”
Section: Discussionmentioning
confidence: 58%
“…2b,c). In a previous study describing 5~-reduced pregnane profiles in captive white rhinoceroses this decline prior to parturition was not seen (Patton et al 1999). However, another study found a decline in FPM during the last two weeks of pregnancy in the captive black rhinoceros (Schwarzenberger et al 1993), although this could also be related to the specificity of the antibody used.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations